(untitled) (Journal of Global Accounting, 2023)
The study examined the effect of corporate social responsibility disclosure on the tax avoidance of listed manufacturing firms on the Nigerian Exchange Group (NGX). The specific objectives of the study are to: examine the effect of social responsibility disclosure on the effective tax rate of quoted manufacturing firms; and, determine the effect of social responsibility disclosure on the book-tax difference of quoted manufacturing firms. The study adopted the ex post facto research design. Out of the population of 72 manufacturing firms, using the judgmental sampling method, twenty-one (21) firms were selected from the Nigerian Exchange Group (NGX). The data used were secondary and were drawn from 2011 to 2019. The data used were sourced from the firm’s annual report, the Nigerian Exchange Group fact book and the Internet. The data collected were analysed using both descriptive and inferential statistical techniques. The hypotheses were analysed using multiple regression; specifically, the Panel Estimated Generalised Least Squares (EGLS) technique. The results showed a significant effect of social responsibility disclosure on the effective tax rate; and, no significant effect of social responsibility disclosure on the book-tax difference. Based on these, the study recommends among others that managers develop models that factor in CSR externalities into share price valuation; and, (potential) investors should pay crucial attention to the CSR stance of managers in publicly listed companies as this may be indicative of the tax avoidance behaviour of the manager and signal several reputational risks in the future.